1995
DOI: 10.1126/science.270.5234.281
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotachylites Generated in Shock Experiments: Implications for Impact Cratering Products and Processes

Abstract: Laboratory hypervelocity impact experiments in which quartz was shock-loaded from 42 to 56 gigapascals imply that type A pseudotachylites form by strain heating and contribute to the loss of strength of rocks in the central uplift of large impact structures. Shock impedance-matched aluminum sample containers, in contrast to steel containers, produced nearly single-wave pressure loading, and enhanced deformation, of silicate samples. Strain heating may act with shock heating to devolatilize planetary materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…Pseudotachylitic breccias are breccias containing a melted rock matrix that resembles pseudotachylite but where the genetic origin of the melt is unclear (Reimold and Gibson, 2005). Potential mechanisms for producing the melt in these breccias include friction melting (Spray and Thompson, 1995), shock melting (Fiske et al, 1995), decompression melting (Reimold and Gibson, 2005) or drainage from the melt sheet above (Lieger et al, 2009, Riller et al, 2010. Pseudotachylitic breccias are abundant in the central uplift of the Vredefort structure and are particularly pervasive in the central core rocks, which were uplifted furthest, from the greatest depth (Reimold and Gibson, 2006).…”
Section: Localized Meltingmentioning
confidence: 99%
“…Pseudotachylitic breccias are breccias containing a melted rock matrix that resembles pseudotachylite but where the genetic origin of the melt is unclear (Reimold and Gibson, 2005). Potential mechanisms for producing the melt in these breccias include friction melting (Spray and Thompson, 1995), shock melting (Fiske et al, 1995), decompression melting (Reimold and Gibson, 2005) or drainage from the melt sheet above (Lieger et al, 2009, Riller et al, 2010. Pseudotachylitic breccias are abundant in the central uplift of the Vredefort structure and are particularly pervasive in the central core rocks, which were uplifted furthest, from the greatest depth (Reimold and Gibson, 2006).…”
Section: Localized Meltingmentioning
confidence: 99%
“…As a result of that deformation, tiny pseudotachylyte-like veins form. The density of these veins increases in direct relation to shock pressure, thereby suggesting that shock veins are shockrelated frictional melt features (Fiske et al 1995). More recently, Kenkmann et al (2000) found frictional melting necessary for vein formation at moderate to low shock pressures.…”
Section: Introductionmentioning
confidence: 96%
“…To investigate the effects of shock-induced shear experimentally, Fiske et al (1995) conducted a shock experiment that allowed variation of strain within a sample of quartz. Upon shock pressure release, lateral deformation, similar to excavation stage deformation upon decompression and gravitational collapse (e.g., Spray and Thompson 1995), allows shear to develop within the sample.…”
Section: Introductionmentioning
confidence: 99%
“…They are found both in impact structures (Reimold 1995) and in undoubted tectonic settings (Sibson 1975). Although experimenters have succeeded in producing melts by direct high-speed frictional sliding (Spray 1995), concern still exists that some melt may be produced by shock compression and release (Reimold 1995), a concern that is bolstered by the formation of pseudotachylite-like melts in shock compression experiments (Fiske et al 1995, Kenkmann et al 2000. Even in these experiments, however, there is a strong possibility that relative sliding among more coherent regions may have produced friction melt at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…He distinguished two basic types of pseudotachylite occurrences. The first, type A, consist of a network of thin (less than 1 mm to several mm) veins that may have formed during the initial shock compression (Fiske et al 1995). Type B pseudotachylites are much larger dike or sill-like bodies that range from cm to several hundred m wide and one or more km long.…”
Section: Introductionmentioning
confidence: 99%